Oblicz wartość wyrażenia dla x = 2 - [latex] sqrt{5} [/latex] i y = 1 + 3[latex] sqrt{5} [/latex]. Wynik zapisz w postaci a + b[latex] sqrt{5} [/latex] gdzie a, b ∈ W a) 3x + y b) x * y c) y : x d) [latex] frac{2y-x}{2x+y} [/latex]

Oblicz wartość wyrażenia dla x = 2 - [latex] sqrt{5} [/latex] i y = 1 + 3[latex] sqrt{5} [/latex]. Wynik zapisz w postaci a + b[latex] sqrt{5} [/latex] gdzie a, b ∈ W a) 3x + y b) x * y c) y : x d) [latex] frac{2y-x}{2x+y} [/latex]
Odpowiedź

a) 3(2-√5) + 1+3√5=6-3√5+1+3√5=7 b) (2-√5)(1+3√5)=2+6√5-√5-15=-13+5√5 c) [latex] frac{1+3 sqrt{5} }{2- sqrt{5} } = frac{(1+3 sqrt{5})(2+ sqrt{5} ) }{(2- sqrt{5})(2+ sqrt{5}) } = frac{2+ sqrt{5}+6 sqrt{5} +15 }{4-5} =frac{17+7sqrt{5} }{-1} =-17-7 sqrt{5} [/latex] d) [latex] frac{2(1+3 sqrt{5})-(2- sqrt{5} ) }{2(2- sqrt{5} )+1+3 sqrt{5} } = frac{2+6 sqrt{5} -2+ sqrt{5} }{4-2 sqrt{5}+1+3 sqrt{5} } = frac{7 sqrt{5} }{5+ sqrt{5} } = frac{7 sqrt{5}(5- sqrt{5} ) }{(5+ sqrt{5})(5- sqrt{5} ) } =[/latex] [latex]frac{7 sqrt{5}(5- sqrt{5} ) }{(5+ sqrt{5})(5- sqrt{5} ) } =frac{35 sqrt{5} -35 }{25-5 } =frac{35 sqrt{5} -35 }{20 } = -frac{7}{4} + frac{7}{4} sqrt{5} [/latex]

[latex]a) 3x+y= 3(2- sqrt{5})+(1+3 sqrt{5}) \ \ 3x+y= 6-3 sqrt{5}+1+3 sqrt{5} \ \ 3x+y= 6+1-3 sqrt{5}+3 sqrt{5} \ \ 3x+y= oxed{7} \ \ \ b) x*y= (2- sqrt{5})*(1+3 sqrt{5}) \ \ x*y= 2+ 6sqrt{5}- sqrt{5}-3( sqrt{5} )^2 \ \ x*y= 2+ 6sqrt{5}- sqrt{5}-3*5 \ \ x*y= 2-15+5sqrt{5} \ \ x*y= oxed{-13+5 sqrt{5}} \ \ [/latex] [latex]c) frac{y}{x}= frac{1+3 sqrt{5} }{2- sqrt{5} } = frac{(1+3 sqrt{5})(2+ sqrt{5} ) }{(2- sqrt{5})(2+ sqrt{5}) } = frac{2+ sqrt{5}+6 sqrt{5} +15 }{(2)^2-( sqrt{5})^2} = \ \ frac{2+15+7sqrt{5} }{4-5} = frac{17+7 sqrt{5} }{-1}= oxed{-17-7 sqrt{5} } [/latex] [latex]d) frac{2y-x}{2x+y} = frac{2(1+3 sqrt{5})-(2- sqrt{5} ) }{2(2- sqrt{5} )+(1+3 sqrt{5}) } = frac{2+6 sqrt{5} -2+ sqrt{5} }{4-2 sqrt{5}+1+3 sqrt{5} } = frac{7 sqrt{5} }{5+ sqrt{5} } = \ \ \ frac{7 sqrt{5}*(5- sqrt{5} ) }{(5+ sqrt{5})*(5- sqrt{5} ) } = frac{35 sqrt{5} -7*( sqrt{5})^2 }{(5)^2-( sqrt{5})^2 } =frac{35 sqrt{5} -35 }{25-5 } = \ \ \ frac{35}{20} sqrt{5}- frac{35}{20} = oxed{ frac{7}{4} sqrt{5} -frac{7}{4} } [/latex] pozdrowienia!!!!

Dodaj swoją odpowiedź